The intralaminar thalamus—an expressway linking visual stimuli to circuits determining agency and action selection - Fisher, Simon; Reynolds, John (Frontiers in Behavioral Neuroscience, 2014)
Anatomical investigations have revealed connections between the intralaminar thalamic nuclei and areas such as the superior colliculus (SC) that receive short latency input from visual and auditory primary sensory areas. The intralaminar nuclei in turn project to the major input nucleus of the basal ganglia, the striatum, providing this nucleus with a source of subcortical excitatory input. Together with a converging input from the cerebral cortex, and a neuromodulatory dopaminergic input from the midbrain, the components previously found necessary for reinforcement learning in the basal ganglia are present. With this intralaminar sensory input, the basal ganglia are thought to play a primary role in determining what aspect of an organism’s own behavior has caused salient environmental changes. Additionally, subcortical loops through thalamic and basal ganglia nuclei are proposed to play a critical role in action selection. In this mini review we will consider the anatomical and physiological evidence underlying the existence of these circuits. We will propose how the circuits interact to modulate basal ganglia output and solve common behavioral learning problems of agency determination and action selection.